(untitled) (PHRASIS | Rivista di studi fraseologici e paremiologici, 2019)
Some verbs are frequent in formal written French language, nonetheless they do not qualify as typical fixed expressions. Linguistic theories on fixedness assume a double – formal and semantic– constraint hypothesis unÀ propos de quelques constructions relationnelles abstraites de l’écrit formel Marie-Pierre Escoubas-Benveniste SAPIENZA UNIVERSITÀ DI ROMA (ITALIA) der which fixed units range from binary phrase to sentence. However, this framework does not seem to allow a satisfactorily description of their textual uses. Primarily, we define the concept of abstract relation verb and introduce the verb properties shown in usage data as an evidence for their borderline phraseologic status. We then demonstrate how the notion of « construction » (Goldberg, 1995) allows to account for the role abstract relational verbs play in text. By giving salience to a grammatical level associated with a logical textual function, the representation of the abstract relational construction (ARC) brings to light a paradigm of verbs that share a given textual function. From an Applied Linguistics standpoint, this approach might offer several benefits.